Applying Simulated Seismic Damage Scenarios in the Volcanic Region of Mount Etna (Sicily): A Case-Study From the MW 4.9, 2018 Earthquake - Pessina, Vera; Meroni, Fabrizio; Azzaro, Raffaele; D’Amico, Salvatore (Frontiers in Earth Science, 2021)
An application for a quick earthquake damage scenario assessment is here presented as a potential tool for planning prevention actions or managing seismic emergencies in the volcanic region of Mt. Etna (Italy). As case-study, we considered the December 26, 2018 earthquake that, with a magnitude MW 4.9, represents the largest event occurring in the area during the last 70 years. The QUEST working group (the INGV macroseismic team) carried out a detailed survey in the damage area, collecting data on the number of buildings in the different vulnerability classes and related damage, with the aim to assign intensity. The maximum intensity reached degree VIII EMS along a narrow strip extending for 5 km astride the Fiandaca fault. In this paper, we simulated the damage scenario in the most struck municipalities of the epicentral area by testing different methodological approaches proposed in the literature using the information of the ISTAT census data collected by the Italian Institute of Statistics. We evaluated the damage level of the residential buildings and we validated the results comparing with the real damage data recognized in the field. Our analysis highlighted the difficulty of applying methods calibrated for larger earthquakes in tectonic domains, to small magnitude events in volcanic zones, where some operating assumptions must be introduced. Despite this, the results confirm the potential of the simulations based on statistical damage assessment methods also in these peculiar conditions, opening the way to finalized plans of pre- and post-earthquake interventions.